الصمت وضجيج السواد في القصيدة الجزائرية - آقطي, نوال (Revues faculté des lettres et des langues, 2014)
يهدف هذا البحث إلى رصد الظاهرة الإيقاعية البصرية للمنشور النصي، حيث ركزت الباحثة في تحليلها على ثلاث ظواهر بصرية تتمثل في سمك الخط وتفتيت النص وتقطيع الكلمة. وأهم ما توصلت إليه الباحثة هو أن التشكيل البصري يفتح أبواب الحوارية بين القارئ والنص، ويجعله يستوعب المضمون.كما أن ارتجاف الكلمة هو ارتجاف حاصل نتيجة الانشقاق النفسي الباطني أو الصراع الخارجي الذي أدى إلى الانقسام    This research aimed to observe the vision rhythmic of textual prism phenomena, the researcher focus in thier analysis on three vision’ phenomena represent in  the line chickness, the text fragments, and the word cutting. The main researcher results that the vision forming open the dialog between there aderand the text, and it lead to understand the implisit content. Also the results assure that the word trembleis a division resulting to the hidden’s psychology fragmentation and the external coflict that lead to division.